Overcoming growing water scarcity: exploring potential improvements in water productivity in India - Amarasinghe, Upali A.; Malik, Ravinder Paul Singh; Sharma, Bharat R. (2010)
Improvements in water productivity (WP) are often suggested as one of the alternative strategies for overcoming growing water scarcity in India. This paper explores the potential improvements in WP of food grains at district level, which currently varies between 0.11 and 1.01 kilogram per cubic metre (kg/m3), in the 403 districts that account for 98% of the total production of food grains. The paper first finds the maximum yield function conditional on consumptive water use (CWU) and then explores the potential improvements in WP by: (a) bridging the gap between actual and maximum yield while keeping CWU constant; and (b) changing the maximum yield by adjusting the CWU using supplementary or deficit irrigation. Deficit irrigation in some areas may decrease yield but can increase production if land availability is not a constraint. A large potential exists for bridging the yield gap in irrigated areas with CWU between 300 and 475 mm. Of the 222 districts that fall under this category, a 50% reduction in yield gap alone could increase production by 100 million tonnes (Mt) without increasing CWU. Supplementary irrigation can increase yield and WP in rain-fed and irrigated areas of 266 and 16 districts with CWU is below 300 mm. Deficit irrigation in irrigated areas of 185 districts with CWU above 475 mm could increase yield, WP and production. Decreasing CWU in irrigated areas with CWU between 425 and 475 mm reduces yield slightly, but if availability of land is not a constraint then the benefits due to water saving and production increases could exceed the cost.